UPAYA MENINGKATKAN KEMAMPUAN KOGNITIF DALAM PENGEMBANGAN KONSEP BILANGAN MELALUI PEMANFAATAN MEDIA GAMBAR - NI NYOMAN SERIADI (EDUKIDS : Jurnal Inovasi Pendidikan Anak Usia Dini, 2022)
This classroom action research aims to determine the increase in cognitive abilities of kindergarten children in group B3 after developing the concept of numbers through the use of picture media in kindergarten children in group B3 Kindergarten in Kuncup Mekar Subagan Karangasem Regency. The type of this research is classroom action research, carried out in several cycles. The subjects of this study were 15 kindergarten children in the B3 group in the first . Research data on the development of the concept of numbers were collected using the assignment method with the instrument format sheet. The research data were analyzed using descriptive analysis methods. The results of data analysis showed that the learning outcomes of conitive abilities in the development of the concept of numbers and the use of image media in the first cycle of 47% which were in the low category turned out to have increased in the second cycle to 100% belonging to the category very high. So,there was an increase in the ability to develop the concept of numbers in children by 53%. ABSTRAKPenelitian tindakan kelas ini bertujuan untuk mengetahui peningkatan kemampuan kognitif Anak setelah pengembangan konsep bilangan melalui pemanfaatan media gambar pada anak TK Kuncup Mekar Subagan Kabupaten Karangasem. Jenis penelitian ini adalah Penelitian Tindakan Kelas yang dilaksanakan dalam beberapa siklus. Subjek penelitian adalah 15 orang anak TK pada kelompok B3 TK Kuncup Mekar Subagan Kabupaten Karangasem. Data penelitian tentang pengembangan konsep bilangan dikumpulkan dengan metoda pemberian tugas dengan instrumen berupa lembar format penugasan. Data hasil penelitian dianalisis dengan menggunakan metode analisis deskriptif. Hasil analisis data menunjukkan bahwa hasil belajar kemampuan kognitif dalam pengembangan konsep bilangan dan pemanfaatan media gambar pada siklus I sebesar 47 % yang berada pada katagori rendah ternyata mengalami peningkatan pada siklus II menjadi 100 % tergolong pada katagori sangat tinggi. Jadi, terjadi peningkatan kemampuan kognitif pengembangan konsep bilangan pada anak sebesar 53 %.